Uji Aktivitas Antibakteri Isolat Endofit Actinomycetes dari Tanaman Kunyit (Curcuma Longa Linn.) dan Lengkuas (Alpinia Galanga) Terhadap Staphylococcus aureus dan Escherichia coli - Hamtini; Citra Amaniah Anhar; Hanny Siti Nuraeni; Ranti Dwi Astriani (JURNAL FARMASI DAN MAKANAN, 2026)
The use of traditional medicine is in great demand because it is relatively safe and rarely causes side effects. Bioactive compounds in plants generally require large biomass to be extracted, so endophytic microbes, especially actinomycetes, are used as an alternative source because they are able to produce secondary metabolites without damaging the host plant. This study aims to isolate and test the antibacterial activity of endophytic actinomycetes from turmeric and galangal plants against Staphylococcus aureus and Escherichia coli. Actinomycete isolation was carried out using Humic Vitamin Agar (HVA) media, and purification using ISP 4 media and continued with antibacterial activity tests. The results of the research showed that of the 26 isolates of endophytic actinomycetes from turmeric and galangal plants that had been isolated, there were 15 isolates that had the ability to inhibit the growth of Staphylococcus aureus and Escherichia coli bacteria. The diameter of the inhibition zone against Staphylococcus aureus ranged from 7.14-14.16 mm, while against Escherichia coli it ranged from 8.11-18.17 mm, with isolate DK4 showing the highest antibacterial activity. These results indicate that endophytic actinomycetes from turmeric and galangal plants have the potential to produce secondary metabolites that are antibacterial.